The theatre of the street: public violence in Antwerp during the first half of the twentieth century - Vrints, Antoon (Crime and city in history, 2020)
"Violence troubles us. Violence disturbs us. Violence gets people moving. In reaction to violent incidents, silent marches regularly pass through the streets of Belgian cities. Many times, thousands of people participate in these protest marches against violence"--